Struktur dan kinerja industri Indonesia dalam era deregulasi dan globalisasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRAK As a country imposing an open economic system, Indonesia will be influenced, sooner or later, by the wave of globalization. This paper identifies, at least, three global waves. Firstly, globalization has accelerated capital mobility which goes hand in hand with a global life-style. Secondly, global investment has led to the growth and spread of transnational corporations throughout the world. Thirdly, global shift has led to the emergence of three megamarkets: ( I ) The European Union, (2) North America, and (3) East and Southeast Asia. Trade blocks have also flourished during this globalization. The major question is, to what extent have globalization and deregulation changed the structure and performance of the Indonesian industrial sector? The study finds the following evidence: Firstly, the prices of major Indonesian commodities are 22 percent higher than their world prices, implying that Indonesia still cannot compete in the world market. Secondly, deregulation measures have contributed immensely to the growth of manufacturing industries as well as to technological improvement. Thirdly, it is the large scale industries and big business groups rather than the small and medium scale industries which have benefited most from deregulation. Fourthly, the calculation of concentration ratios indicates that, on average the market structure of the Indonesian manufacturing industry is oligopolistic. Furthermore, industrial performance analysis shows that the higher concentration ratio correlates positively with the lower export-orientation. Keywords: industrial performance